Polygamy and early marriage in the Dutch East Indies - Maulidah, Alvin; Agung, Dewa Agung Gede; Sayono, Joko (UNIVERITAS PGRI MADIUN, 2024)
The article discusses the role of Poetri Mardika in suppressing early marriage and polygamy during the colonial period in the Dutch East Indies. Poetri mardika was the first women's organization in 1912 during the national movement by boedi oetomo. The organization consisted of women and men who cared about the fate of women. They voiced their ideas through magazines. The position of women who are shackled by customary support makes them powerless to voice their rights. The research aims to examine polygamy and early marriage in colonial society using historical methods, namely heuristics, criticism, interpretation and historiography. Heuristics were conducted by collecting primary sources from magazines and secondary books and journals with the keywords polygamy and early marriage. Criticism of primary and secondary data is internally selected to determine the authenticity of the source. Interpretation uses the lewis coser conflict approach. The result of the research is that the practice of early marriage occurs because the social system of society shackles and there is no power for women to reject the system. Meanwhile, polygamy that occurred in the 1900s had different intensities in each region. This practice had a negative impact on women, so Poetri Mardika tried to raise their status by paying attention through education and teaching. Through education, women can be independent and no longer depend on men so that they can express their rights and obligations without being hindered by the confinement of men.